Effect of Probiotic (Alkalihalobacillus) in the Outcome of Acute Watery Diarrhea in Children Admitted in Combined Military Hospital Rawalpindi, Pakistan - Iqbal, Junaid; Anwar, Sofia; Hasan, Shamama; Naveed, Maliha; Ikram, Farooq; Sahaf, . (Biological and Clinical Sciences Research Journal, 2025)
Acute watery diarrhea remains a leading cause of child mortality globally. Probiotics like Alkalihalobacillus have shown promise in reducing diarrhea duration, but localized data from Pakistan is limited. This study evaluated the efficacy of Alkalihalobacillus probiotics in hospitalized children (1–5 years) with acute watery diarrhea. Methods: An analytical cross-sectional study was conducted at CMH Rawalpindi over six months from August 2024 to February 2025.Thirty-eight children were equally divided into standard therapy (ORS/IV fluids) and probiotic groups (standard therapy + Alkalihalobacillus). Outcomes included diarrhea duration, stool frequency, hospital stay, and clinical improvement. Results: This study evaluated standard therapy along with Alkalihalbacillus probiotics versus standard therapy in children (1-5 years) with acute watery diarrhea. The probiotic group showed significantly better outcomes: shorter diarrhea duration (2.26 vs 3.26 days, p<0.001), reduced hospitalization (2.79 vs 3.32 days, p<0.001), faster recovery (2.53 vs 3.42 days, p<0.001), and doubled stool normalization rates (63.2% vs 36.8%). Probiotics also improved discharge stool frequency (2.21 vs 2.63/day, p=0.008), demonstrating superior efficacy. Conclusion: Alkalihalobacillus probiotics significantly accelerated recovery and reduced hospitalization but had mixed effects on stool consistency. While effective as adjunct therapy, their impact on long-term prevention remains inconclusive.